Introducing Querciphoma styphnolobii sp. nov., the first sexual morph of Querciphoma (Leptosphaeriaceae, Pleosporales) - Gao, Hanxing; Yin, Jingyan; Li, Yu; Liu, Shuyan; Zhu, Zhaoxiang (Phytotaxa, 2022)
Using combined morphological characteristics and molecular phylogeny, a new species Querciphoma styphnolobii sp. nov. (Dothideomycetes, Pleosporales) from China is described and illustrated. The new species is distinguished by dark green to black colony, eustromatic conidiomata, smooth, hyaline, cylindrical conidia with one middle constricted, septate and muriform ascospores. Phylogenetic analyses using multilocus sequence data of internal transcribed spacers (ITS), large subunit 28S rDNA (LSU), small subunit 18S rDNA (SSU), and translation elongation factor 1-alpha (TEF1-α) regions revealed that Q. styphnolobii is closely related to Q. minuta in Leptosphaeriaceae. The sexual stage of Querciphoma is characterized by superficial, rough, or hairy ascomata, cellular pseudoparaphyses, ellipsoidal and muriform ascospore with a multi-transverse vertical septum.